Review on Adaptive Indexing Method for Effective Retrieval of streaming Data - Rani, P.K.Usha; Madhavi, K. Reddy (International Journal of Computer Sciences and Engineering, 2025)
With the heterogenous data generated from large volumes of sensor networks, internet, telecommunications, current data becomes huge on big data. To handle these types of data efficient query processing techniques are necessary. As data keep on changing dynamically, an efficient clustering and indexing method is needed for continuously processing the data streams. Dynamic data can be partitioned into number of clusters, then followed by indexing. This project uses a new index structure called adaptive clustering, which is a combination of cluster and block based techniques, for processing data streams like stock market data .The incoming data which is dynamically entering is first clustered and later indexed using adaptive techniques. Experimental analysis will be made with the existing techniques in terms of space, cost, scalability and rate of retrieval.